Analysis of Three Phase Nine Level Diode Clamped Multi Level Inverter. Issue 1 (February 2021) - Nagarajan, L; Anne Rosaline, A; Baladhandapani, R; Nazar Ali, A; Stonier, Albert Alexander
Abstract: Compared to conventional inverter (square wave) multi-level inverter offers quality power owing to different voltage levels utilization in average and high voltage. Besides it also reduces Total Harmonic Distortion in the distributed system and dv/dt across power switches. This advantage is transcendently appropriate for cascaded diode connected converter that can be worked to create more number of levels using asymmetrical voltage source because of their integrated arrangement. However, this benefit no longer exist because it requires many dc links (batteries or rectifiers) which is costlier. Substitute method of implementing single low voltage floating DC link is to recompense voltage distortion using Neutral-Point-Clamped (NPC) converter. This NPC output and controlled floating single DC-link voltage along with controlled PWM strategy reduces the THD. This improves the bandwidth and make simpler the current control scheme. These motivated the study and analyze the performance of a Diode Clamp based three phase nine level multilevel inverterusingnovel PWM approaches in MATLAB 2014b and PROTEUS for hardware development. Thus low power prototype is developed and its performance is shown.